Hedonic Profile and Spoilage Detection of Mackerel Tuna Fish Balls Preserved with Coconut Shell Liquid Smoke During Storage - Eli Purwanti; Juliani Juliani; Ruka Yulia (Universitas Serambi Mekkah, 2022)
The processing of mackerel tuna-based food products is still very limited, so efforts to diversify other mackerel tuna-based food products are needed. One of the products that can be made from fish meat is fishballs. Fishballs are a nutrient-rich product with a high-water content so that the product quickly became spoilage when stored at room temperatures. Liquid smoke is reported to have been used as a natural preservative. However, there are no reports regarding mackerel tuna fishballs that soaking in coconut shell liquid smoke could affect the consumer's preference on hendonic properties such as color, aroma, taste and texture. The product was analyzed using hedonic test is a test for color, aroma, taste, texture. The data was analyzed descriptively. The result shows that color preference of average 3.92 (likes), aroma preference of average 3.22 (likes), taste preference of average 3.81 (likes), and texture preference of average 3.26 (likes). Based on spoilage detection which shows spoilage characteristics such as off odor, off flavor, and acidity so that shelf life of mackerel tuna fishballs preserved with coconut shell liquid smoke predicted less than 5 days and more than three days at room temperatures. Keywords: Euthynnus Affinis, Organoleptic, Sensory-Based Detection, Food Diversification